2021
DOI: 10.1021/acs.jpcc.1c02415
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Insights into Electrical and Transport Properties of Chloroaluminate Ionic Liquids for Aluminum-Ion Batteries

Abstract: Around the world, there is a critical need for sustainable energy storage systems for grid-level stationary energy storage. In the search for such systems, aluminum (Al)-ion batteries have recently attracted considerable attention due to their positive attributes including low cost, high abundance of raw materials, and long cycling life. Among all, chloroaluminate ionic liquid (IL) composed of aluminum chloride (AlCl 3 ) and a Lewis basic organic chloride (XCl) is the most widely employed electrolyte system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Zhu et al reported conductivities increasing from 15 to 17.5 mS cm –1 for AlCl 3 :EMIM-Cl liquid for mole ratios between 1.4:1 and 1.7:1 (LA:LB) . Conversely, Azimi et al reported conductivities decreasing from 22.6 to 14.7 mS cm –1 for LA:LB compositions between 1:1 and 2:1 with AlCl 3 :EMIM-Cl liquids . Other reports have found conductivities of 16.1, 15.5, and 9.2 mS cm –1 for AlCl 3 :EMIM-Cl liquids with a 1.5:1 mole ratio.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Zhu et al reported conductivities increasing from 15 to 17.5 mS cm –1 for AlCl 3 :EMIM-Cl liquid for mole ratios between 1.4:1 and 1.7:1 (LA:LB) . Conversely, Azimi et al reported conductivities decreasing from 22.6 to 14.7 mS cm –1 for LA:LB compositions between 1:1 and 2:1 with AlCl 3 :EMIM-Cl liquids . Other reports have found conductivities of 16.1, 15.5, and 9.2 mS cm –1 for AlCl 3 :EMIM-Cl liquids with a 1.5:1 mole ratio.…”
Section: Introductionmentioning
confidence: 95%
“…These electrolytes, often called chloroaluminate liquids, are formed by an acid–base reaction between a Lewis acid (LA; i.e., AlCl 3 salt) and a Lewis base (LB; e.g., Cl – -containing salt). To date, the majority of research has been done on chloroaluminate liquids made from the solid (at room temperature) salt 1-ethyl-3-methylimidazolium chloride (EMIM-Cl); this electrolyte is commercially available . The electrochemical and rheological performance is promising, but it comes with a high economic cost of the starting material, which ultimately is not advantageous for scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting Information is available from the Wiley Online Library or from the author. Additional references cited within the Supporting Information [36–38] …”
Section: Supporting Informationmentioning
confidence: 99%
“…The chloroaluminate IL prepared by mixing AlCl 3 and trimethylamine hydrochloride (TMAHCl) at a molar ratio of 1.8 was used as the electrolyte. Compared with the widely adopted EMImCl‐based chloroaluminate IL electrolyte, the higher anolyte capacity of the AlCl 3 ‐TMAHCl electrolyte due to the lower molar mass of TMAHCl (Supporting Information Figure S2) and the lower cost of TMAHCl further enhance the performance and sustainability of the resulting battery systems [28] . A schematic of the assembled cell and mechanism is presented in Figure 1(a).…”
Section: Figurementioning
confidence: 99%
“…Compared with the widely adopted EMImCl-based chloroaluminate IL electrolyte, the higher anolyte capacity of the AlCl 3 -TMAHCl electrolyte due to the lower molar mass of TMAHCl (Supporting Information Figure S2) and the lower cost of TMAHCl further enhance the performance and sustainability of the resulting battery systems. [28] A schematic of the assembled cell and mechanism is presented in Figure 1(a). During cycling, the reversible intercalation/deintercalation of AlCl 2 + was achieved at the carbonyl sites (C=O) of BDTD, contribute to the reversible capacity over cycles (Figure 1a).…”
mentioning
confidence: 99%